FORENSIC MEDICAL ASSESSMENT OF PATHOMORPHOLOGICAL SIGNS IN THE MYOCARDIUM IN STAB WOUNDS - S.Sh.Gamidov; S.A.Khakimov (TADQIQOTLAR, 2025)
Pathomorphological characteristics of myocardium resulting from injuries to the heart are described with reference to their localization in different regions of the wound canal at different time periods after the injury. The studies were carried out with the use of light microscopy.